Development of computer inventory system using automatic data gathering and barcode for FTMSK / Mohd Hafidzi Mat Yasin - Mat Yasin, Mohd Hafidzi (2007)
Computer system inventory is an important subject in management. Having reliable computer inventory data will help the staff in managing computer assets, especially when they are going to trace the computers and peripheral and do mass upgrade. The purpose of the system is to help the staffs manage the computers inventory more effective and easy way. Using this Computer Inventory System, staffs can get information about all computers, monitors and other peripherals that currently exist in the faculty. They also can trace where all the computers are located in the faculty whether in the computer labs, classes, offices, in the lecturer’s room or anywhere in the faculty. The main feature of this system is using Automatic Data Gathering and Barcode system. The staff no longer needs to key in all the data about the computer specifications into the system but only the serial number and the location of the computer. The staff just can sit in their room waiting for the computer data and manage from their room. The methods that will be used to gather information for this research are done by experiment. The system architectures that are used to develop this system are XAMP which is the combination of Apache Web Server, MySQL Database Server, PHP and PhpMyAdmin, PC and barcode scanner. This system can be accessed using web browser that have internet connection and managed by the Administrator and the staffs. This solution will enable the staff reduce time and can manage the computer inventory effectively and more efficient.